Associations between cognitive-emotion regulation, social support and physical strength towards psychological well-being among graduate students - M. Munisamy, Thamarai; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The research was conducted to examine the associations between cognitive-emotion regulation, social support and physical strength towards the psychological well-being of graduate students. Four instruments were used in this research namely Psychological Well-being by Ryff C. (1989), Cognitive-Emotion Regulation by Garnefsky N. and Kraaij V. (2006), Multidimensional Scale of Perceived Social Support by Greg Zimet (1988) and Exercise Habit Strength Questionnaire by Grove & Ortega (2005). A total of 3426graduate students (2124 females and 1302 males) were randomly selected in one Malaysian university. Data were analyzed using an independent t-test, Pearson correlation, and multiple regressions. The finding of this study revealed that the self-blame and negative consequences were the most significant factors influencing psychological well-being. The findings of the study also explained that students scored highest in the strategy of other-blame for cognitive-emotion regulation. With regard to social support, graduate students received support from significant others more than friends and family. With respect to exercise habit strength, strong stimulus-response scored the highest mean compared to other sub-factors.